2008
DOI: 10.1194/jlr.m700167-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation of drug action on lipoprotein metabolism-related targets

Abstract: Genetic analysis has shown that the slower than normal rhythmic defecation behavior of the clk-1 mutants of Caenorhabditis elegans is the result of altered lipoprotein metabolism. We show here that this phenotype can be suppressed by drugs that affect lipoprotein metabolism, including drugs that affect HMG-CoA reductase activity, reverse cholesterol transport, or HDL levels. These pharmacological effects are highly specific, as these drugs affect defecation only in clk-1 mutants and not in the wild-type and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…We have previously shown that the defecation cycle of clk-1 mutants, but not that of the wild type, is suppressed by lowering the levels of dietary cholesterol from 5 µg/ml to 2 µg/ml [23]. We have now extended this observation to the effect of high cholesterol (50 µg/ml), which has no effect on the wild type but further slows down the defecation of clk-1(qm30) mutants (Figure 3B).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…We have previously shown that the defecation cycle of clk-1 mutants, but not that of the wild type, is suppressed by lowering the levels of dietary cholesterol from 5 µg/ml to 2 µg/ml [23]. We have now extended this observation to the effect of high cholesterol (50 µg/ml), which has no effect on the wild type but further slows down the defecation of clk-1(qm30) mutants (Figure 3B).…”
Section: Resultsmentioning
confidence: 55%
“…Given the known function of MTP it was concluded that a type of MTP-dependent, LDL-like lipoprotein, distinct from yolk, affects the rate of defecation [14]. Reducing the level of dietary cholesterol mimics the effects of dsc-4 on the defecation cycle length of clk-1 mutants [15], [23]. These observations suggest that clk-1 mutants have slow defecation because they have high levels of LDL-like lipoproteins biosynthesis and secretion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were scored as adults after they had undergone the final molt and a vulva could be observed. Defecation cycle rates and pharyngeal pumping rate were measured as previously described 11, 46 .…”
Section: Methodsmentioning
confidence: 99%
“…Several observations suggest that dsc-4/mtp suppresses clk-1 by reducing the level of a type of MTP-dependent, LDL-like lipoprotein. For example, reducing the level of dietary cholesterol, which is a major constituent of lipoproteins whose reduction leads to reduce LDL levels in vertebrate, mimics the effects of dsc-4 on the slow germline development and the slow defecation cycle length of clk-1 mutants, 28 , 32 suggesting that those phenotypes of clk-1 mutants are due to high levels of LDL-like lipoproteins biosynthesis and secretion. It is not clear how elevated lipoprotein biosynthesis and secretion slow down the defecation cycle; however, the MTP-dependent lipid transport system appears to be so well conserved between mammals and C. elegans that drugs that have been developed to lower lipid levels in humans can act as suppressors of the slow defecation phenotype of clk-1 mutants 32 .…”
Section: Cholesterol Transport Through Lipoproteins Distinct From Yolkmentioning
confidence: 99%